Multi-site studies and field studies - Rajashekhar, Geetha (Henry Stewart Talks, 2012)
Conduct of multi-site and field studies in compliance with the OECD Principles of GLP, Context, issues and complexities, Responsibilities of test facility and test site personnel and sponsor, Importance of communication, Master schedule requirements for test sites, Study plan requirements (with special reference to flexibility required for field studies), Performance of the study (with special reference to general facilities and to facilities for handling test and reference items and documentation required for field studies), Equipment, control and accountability of study materials for multi-site studies, Reporting of study results, Standard Operating Procedures, Archives